EFFECTIVE MECHANISMS OF FIGHTING SPIRITUAL-IDEOLOGICAL THREATS IN THE CONDITIONS OF GLOBALIZATION - Meyliyev Ulmas Farmonovich (American Journals, 2024)
This article discusses globalization, ideological threat, popular culture, popular culture in the development of society, ideology.
Keywords: Globalization, ideological threat, mass culture, society, culture, ideology, idea, national idea, nation, spirituality, traditional attack, threat.